2013
DOI: 10.1111/jcmm.12167
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychological stress activates BMP4‐dependent extramedullary erythropoiesis

Abstract: Psychological stress affects different physiological processes including haematopoiesis. However, erythropoietic effects of chronic psychological stress remain largely unknown. The adult spleen contains a distinct microenvironment favourable for rapid expansion of erythroid progenitors in response to stressful stimuli, and emerging evidence suggests that inappropriate activation of stress erythropoiesis may predispose to leukaemic transformation. We used a mouse model to study the influence of chronic psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…The initial sympathetic response following trauma is a necessary physiologic response but when this stressful state is prolonged it impacts many organs. This finding is supported by the work of Vignjevic et al 30 who demonstrated that psychological stress alone activates extramedullary erythropoiesis in adult mice.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The initial sympathetic response following trauma is a necessary physiologic response but when this stressful state is prolonged it impacts many organs. This finding is supported by the work of Vignjevic et al 30 who demonstrated that psychological stress alone activates extramedullary erythropoiesis in adult mice.…”
Section: Discussionsupporting
confidence: 65%
“…Yet, chronic stress alone in mice did not increase the total number of Ter119 positive cells after seven days. 30 It took 14 days of restraint stress to increase the number of Ter119 positive cells suggesting that chronic stress led to a delay in terminal erythroid differentiation. 30 This confirms that extramedullary erythropoiesis in the spleen works rapidly to produce mature erythroid cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The erythropoietic growth factors BMP2 or 7 are unlikely to account for the induction of extramedullary hematopoiesis, since they are ligands for ActRIIB.hFc. A similar situation exists for BMP4, another ActRIIB.hFc ligand that has previously been shown to induce extramedullary hematopoiesis in mice57. Interestingly, the type III TGF-β receptor has been shown to be a marker that distinguishes ‘early' and ‘late' burst-forming unit erythroid progenitors58.…”
Section: Discussionmentioning
confidence: 70%